Porous carbon as well as preparation method and application thereof

By controlling the mass ratio of resin and electrolyte and the water vapor activation temperature, porous carbon is prepared, which solves the problems of low capacity retention and volume expansion of nano-silicon carbon anode material, improves capacity retention and extends cycle life, and improves lithium-ion batteries performance.

CN119306218AActive Publication Date: 2025-01-14JINLONGYU NEW ENERGY (SHENZHEN) CO LTD

Patent Information

Application Number
CN202411366904.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-23
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The capacity retention rate of nano-silicon carbon anode material is low and the volume expands severely during charging and discharging, resulting in short cycle life and reduced performance.

Method used

By controlling the mass ratio of resin and electrolyte and the water vapor activation temperature, porous carbon is prepared, the interface conditions of nano-silicon carbon anode materials are improved, the generation of SEI film is inhibited, the brittleness and pore size of porous carbon is regulated, the capacity retention rate is improved, and volume expansion is reduced .

Benefits of technology

The capacity retention rate of nano-silicon carbon anode material is significantly improved, the volume expansion during charging and discharging is reduced, the cycle life is extended, and the performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066481560000071
    Figure BDA0005066481560000071
  • Figure BDA0005066481560000072
    Figure BDA0005066481560000072
  • Figure BDA0005066481560000081
    Figure BDA0005066481560000081
Patent Text Reader

Abstract

The invention discloses porous carbon and a preparation method and application thereof, and the preparation method of the porous carbon comprises the following steps: S1, mixing resin and electrolyte in a solvent, and carrying out spray drying to obtain a porous carbon precursor; s2, pre-carbonizing the porous carbon precursor, and activating the porous carbon precursor by using water vapor to obtain porous carbon; in the step S1, the mass ratio of the resin to the electrolyte is 100: (0.1-5); in the step S2, the activation temperature is 500 to 1200 DEG C. According to the preparation method of the porous carbon, by controlling the mass ratio of the resin to the electrolyte and the activation temperature of the water vapor, the interface condition of the nano silicon-carbon negative electrode material prepared from the porous carbon is improved, generation of a new SEI film is inhibited, the capacity retention rate of the nano silicon-carbon negative electrode material prepared from the porous carbon is increased, and the service life of the nano silicon-carbon negative electrode material is prolonged. And the volume expansion of the nano silicon-carbon negative electrode material during charging and discharging is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and more specifically, to porous carbon and a preparation method and application thereof. Background Art

[0002] The actual specific capacity of graphite negative electrode materials at present is 360-365mAh / g, which is close to the theoretical specific capacity of 372mAh / g. Therefore, improving the performance of graphite negative electrode materials has little effect on improving the performance of lithium-ion batteries. Silicon-based negative electrode materials have the advantages of high energy density and wide distribution of raw materials, and are considered to be the most promising negative electrode materials for the next generation of lithium-ion batteries. Silicon-based negative electrode materials mainly include single-element silicon negative electrode materials, silicon oxide negative electrode materials and nano-silicon carbon negative electrode materials. Among them, the preparation method of nano-carbon negative electrode materials includes depositing silicon onto a porous carbon skeleton using chemical vapor deposition (CVD).

[0003] Nanocarbon negative electrode materials have excellent performance in multiple dimensions such as gram capacity, first effect, number of cycles, and rate. In terms of production, nanocarbon negative electrode materials can reduce pre-lithium and pre-magnesium processes, and have the potential to significantly reduce costs compared to silicon dioxide negative electrode materials. However, on the one hand, the capacity retention rate of nanocarbon negative electrode materials is low, resulting in a short cycle life; on the other hand, as the capacity increases, the volume of nanocarbon negative electrode materials expands severely during charging and discharging, causing the material to crack or even pulverize, destroying the contact between the nanocarbon negative electrode material and the current collector, and having an adverse effect on the performance of lithium-ion batteries.

[0004] Therefore, it is of great significance to develop a new porous carbon to improve the capacity retention rate of nano-silicon-carbon negative electrode materials and reduce the volume expansion of nano-silicon-carbon negative electrode materials during charging and discharging. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of low capacity retention rate of nano silicon carbon negative electrode materials and volume expansion of nano silicon carbon negative electrode materials during charge and discharge in the prior art, and to provide a porous carbon and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing porous carbon, the preparation method comprising the following steps:

[0008] S1. mixing a resin and an electrolyte in a solvent, and obtaining a porous carbon precursor by spray drying;

[0009] S2. Pre-carbonizing the porous carbon precursor and then activating it with water vapor to obtain porous carbon;

[0010] In step S1, the mass ratio of the resin to the electrolyte is 100:(0.1-5);

[0011] In step S2, the activation temperature is 500-1200°C.

[0012] The preparation method of porous carbon of the present invention improves the interface condition of nano silicon carbon negative electrode material prepared by using porous carbon, inhibits the generation of new SEI film, improves the capacity retention rate of nano silicon carbon negative electrode material prepared by using porous carbon, and reduces the volume expansion of nano silicon carbon negative electrode material during charging and discharging by controlling the mass ratio of resin and electrolyte and the activation temperature of water vapor; at the same time, by controlling the activation temperature of water vapor, the brittleness and pore size of porous carbon are also regulated, which is beneficial to improve the capacity retention rate of nano silicon carbon negative electrode material prepared by using porous carbon and reduce the volume expansion of nano silicon carbon negative electrode material during charging and discharging.

[0013] In particular, when the mass ratio of resin to electrolyte and the activation temperature of water vapor are too high or too low, it is not conducive to improving the interface conditions of nano silicon carbon negative electrode materials, and it is impossible to inhibit the formation of SEI film, improve the capacity retention rate of nano silicon carbon negative electrode materials prepared using porous carbon, and reduce the volume expansion of nano silicon carbon negative electrode materials during charging and discharging.

[0014] In addition, when the activation temperature of water vapor is too high, the brittleness of porous carbon will increase, making the porous carbon prone to cracking and structural collapse, which is not conducive to improving the capacity retention rate of nano-silicon-carbon negative electrode materials prepared using porous carbon and reducing the volume expansion of nano-silicon-carbon negative electrode materials during charging and discharging; and when the activation temperature of water vapor is too low, the pore size of porous carbon will be too small, that is, the activation is incomplete, affecting the silicon deposition and carbon coating of porous carbon in the process of preparing nano-silicon-carbon negative electrode materials, which is not conducive to improving the capacity retention rate of nano-silicon-carbon negative electrode materials prepared using porous carbon and reducing the volume expansion of nano-silicon-carbon negative electrode materials during charging and discharging.

[0015] Preferably, in step S1, the mass ratio of the resin to the electrolyte is 100:(1-5).

[0016] Preferably, in step S2, the activation temperature is 600-1100°C.

[0017] Preferably, in step S1, the resin is at least one of polyester resin, polyamide resin, phenolic resin and polyvinyl chloride resin.

[0018] Polyester resins, polyamide resins, phenolic resins, and polyvinyl chloride resins commonly used in the art can all be used in the present invention.

[0019] Preferably, in step S1, the electrolyte is at least one of LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate), and LLZO (lithium lanthanum zirconium oxide).

[0020] Commercially available LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate), and LLZO (lithium lanthanum zirconium oxide) commonly used in the art can all be used in the present invention.

[0021] More preferably, the chemical composition general formula of the LATP (lithium aluminum titanium phosphate) is Li 1+c Al c Ti 2-c (PO4)3, 0 < c ≤ 0.5.

[0022] More preferably, the chemical composition general formula of the LLTO (lithium lanthanum titanate) is Li 3e La 2 / 3-e Ti f T 1-f O3, 0 < e < 2 / 3, 0 < f ≤ 1, where T is independently selected from at least one of Nb, W, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, and Se.

[0023] More preferably, the chemical composition general formula of the LLZO (lithium lanthanum zirconium oxide) is Li 7-d La3Zr 2-d O 12 , 0 < d ≤ 0.7.

[0024] In the present invention, the LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate), and LLZO (lithium lanthanum zirconium oxide) can be obtained commercially or prepared by conventional preparation methods in the art. Herein, a preparation method for each of LATP, LAGP, and LLZO is provided specifically:

[0025] The preparation method of the LATP (lithium aluminum titanium phosphate) is as follows:

[0026] Weigh the Li source, Al source, Ti source, and P source according to the molecular stoichiometric ratio, mix them, and heat-treat at 800 - 950 °C for 6 - 20 h to obtain LATP; among them, the Li source can be selected but not limited to lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, etc., the Al source can be selected but not limited to alumina, aluminum nitrate, aluminum phosphate, aluminum isopropoxide, etc., the Ti source can be selected but not limited to titanium oxide, tetrabutyl titanate, titanium carbide, titanium pyrophosphate, etc., and the P source can be selected but not limited to ammonium dihydrogen phosphate, phosphorus pentoxide, titanium pyrophosphate, etc.

[0027] The preparation method of the LLTO (lithium lanthanum titanate) is as follows:

[0028] Li source, La source, Ti source and T source are weighed according to the molecular stoichiometric ratio, mixed, and heat treated at 1000-1200°C for 6-20h to obtain LLTO; wherein the Li source may be selected from but not limited to lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, etc., the La source may be selected from but not limited to lanthanum oxide, lanthanum fluoride, lanthanum acetate, etc., the Ti source may be selected from but not limited to titanium oxide, tetrabutyl titanate, titanium carbide, titanium pyrophosphate, etc., and the T source is at least one of the oxides and carbonates of Nb, W, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, and Se.

[0029] The preparation method of the LLZO (lithium lanthanum zirconium oxide) is:

[0030] Li source, La source and Zr source are weighed according to the molecular stoichiometric ratio, mixed, and heat-treated at 900-1000° C. for 4-8 hours to obtain LLZO; wherein the Li source may be selected from but not limited to lithium carbonate, lithium hydroxide, lithium monohydrogen phosphate, lithium dihydrogen phosphate, etc., the La source may be selected from but not limited to lanthanum oxide, lanthanum carbonate, lanthanum nitrate, lanthanum hydroxide, etc., and the Zr source may be selected from but not limited to zirconium oxide, zirconium carbonate, zirconium nitrate, zirconium hydroxide, etc.

[0031] In the present invention, "weighing by molecular weight ratio" means weighing by the ratio of the amount of each element in the general chemical composition formula (i.e., molar ratio). For example, the general chemical composition formula of LATP (lithium aluminum titanium phosphate) is Li 1+c Al c Ti 2-c (PO4)3, in the preparation method of LATP, "weighing according to molecular stoichiometric ratio" specifically refers to weighing the Li source, Al source, Ti source, and P source respectively according to the ratio of the amount of substances of the elements Li, Al, Ti, and P (i.e., molar ratio) (1+c):c:(2-c):3.

[0032] Preferably, in step S1, the solvent is at least one of ethanol, methanol, ethylene glycol, ethylene triol, n-butanol, propylene glycol and butanol.

[0033] Preferably, in step S1, the solid-liquid ratio of the resin to the solvent is (1-30) g: (70-99) mL.

[0034] Preferably, in step S1, the spray drying temperature is 60°C-180°C, the solution feed flow rate is 3-30 L / min, and the atomization pressure is 0.01-2 MPa.

[0035] Preferably, in step S2, the pre-carbonization temperature is 400-900°C.

[0036] More preferably, in step S2, the pre-carbonization temperature is 650-800°C.

[0037] In the present invention, the pre-carbonization temperature will also affect the brittleness and pore size of the porous carbon. If the pre-carbonization temperature is too high, the brittleness of the porous carbon will increase, making the porous carbon more prone to fragmentation and structural collapse, and it is impossible to increase the capacity retention rate of the nano-silicon-carbon negative electrode material prepared using the porous carbon and reduce the volume expansion of the nano-silicon-carbon negative electrode material during charge and discharge. If the pre-carbonization temperature is too low, it will affect the carbonization degree of the porous carbon material, making the pore size of the porous carbon more likely to be smaller, and the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano-silicon-carbon negative electrode material are also more easily affected, and it is impossible to increase the capacity retention rate of the nano-silicon-carbon negative electrode material prepared using the porous carbon and reduce the volume expansion of the nano-silicon-carbon negative electrode material during charge and discharge.

[0038] Preferably, in step S2, the pre-carbonization time is 0.5-4h.

[0039] Preferably, in step S2, the pre-carbonization is performed under the protection of an inert gas, and the inert gas is at least one of nitrogen, helium, neon and argon.

[0040] Preferably, in step S2, the activation time is 2-8 hours.

[0041] In a second aspect, the present invention provides a porous carbon prepared by the preparation method described in the first aspect.

[0042] Preferably, the median particle size (D50) of the porous carbon is 1.5-15 μm, and the specific surface area is 800-2000 m 2 / g, pore size is 0.5-2nm.

[0043] More preferably, the median particle size (D50) of the porous carbon is 5.0-6.5 μm, and the specific surface area is 1100-2000 m 2 / g, pore size is 1.5-2.0nm.

[0044] More preferably, the median particle size (D50) of the porous carbon is 5.21-6.01 μm, and the specific surface area is 1176-1987 m 2 / g, pore size is 1.5667-1.9244nm.

[0045] In a third aspect, the present invention provides an application of porous carbon in negative electrode materials.

[0046] In a fourth aspect, the present invention provides a method for preparing a nano silicon-carbon negative electrode material, the preparation method comprising the following steps:

[0047] S1. Under inert gas protection, silicon is deposited on the porous carbon as described in the second aspect by chemical vapor deposition (CVD) using a silicon source gas to obtain a nano-silicon carbon precursor;

[0048] S2. Under the protection of inert gas, the nano silicon carbon precursor is carbon coated by using carbon source gas through chemical vapor deposition (CVD) to obtain the nano silicon carbon negative electrode material.

[0049] Preferably, in step S1, the silicon source gas is at least one of monosilane, disilane, dichlorosilane, silicon tetrachloride, dichlorodihydrosilane and trichlorosilane.

[0050] Preferably, in step S1 and / or step S2, the inert gas is at least one of nitrogen, helium, neon and argon.

[0051] Preferably, in step S1, the flow rate ratio of the silicon source gas and the inert gas is (0.1-0.5):1.

[0052] Preferably, in step S1, the silicon deposition temperature is 400-700° C. and the time is 1-6 hours.

[0053] Preferably, in step S2, the carbon source gas is at least one of acetylene, methane, propane and cyclohexane.

[0054] Preferably, in step S2, the flow rate ratio of the carbon source gas and the inert gas is (0.1-0.5):1.

[0055] Preferably, in step S2, the carbon coating is carried out at a temperature of 400-800°C and for a time of 1-6 hours.

[0056] In a fifth aspect, the present invention provides a nano silicon-carbon negative electrode material prepared by the preparation method described in the fourth aspect.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The preparation method of porous carbon of the present invention improves the interface condition of nano silicon carbon negative electrode material prepared by using porous carbon, inhibits the generation of new SEI film, improves the capacity retention rate of nano silicon carbon negative electrode material prepared by using porous carbon, and reduces the volume expansion of nano silicon carbon negative electrode material during charging and discharging by controlling the mass ratio of resin and electrolyte and the activation temperature of water vapor; at the same time, by controlling the activation temperature of water vapor, the brittleness and pore size of porous carbon are also regulated, which is beneficial to improve the capacity retention rate of nano silicon carbon negative electrode material prepared by using porous carbon and reduce the volume expansion of nano silicon carbon negative electrode material during charging and discharging.

[0059] In the present invention, the pre-carbonization temperature will also affect the brittleness and pore size of the porous carbon. If the pre-carbonization temperature is too high, the brittleness of the porous carbon will increase, making the porous carbon more prone to fragmentation and structural collapse, and it is impossible to increase the capacity retention rate of the nano-silicon-carbon negative electrode material prepared using the porous carbon and reduce the volume expansion of the nano-silicon-carbon negative electrode material during charge and discharge. If the pre-carbonization temperature is too low, it will affect the carbonization degree of the porous carbon material, making the pore size of the porous carbon more likely to be smaller, and the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano-silicon-carbon negative electrode material are also more easily affected, and it is impossible to increase the capacity retention rate of the nano-silicon-carbon negative electrode material prepared using the porous carbon and reduce the volume expansion of the nano-silicon-carbon negative electrode material during charge and discharge. DETAILED DESCRIPTION

[0060] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0061] The experimental methods without specific conditions in the following examples, comparative examples, application examples and comparative application examples are generally carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0062] In each embodiment and comparative example of the present invention, the use of reagents is as follows:

[0063] The chemical formula of LATP (lithium aluminum titanium phosphate) is Li 1.4 Al 0.4 Ti 1.6 (PO4)3, the preparation method thereof is as follows: lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate are weighed according to a molecular stoichiometric ratio (i.e., the molar ratio of lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate is 0.7:0.2:1.6:3), mixed, and heat treated at 800°C for 15h to obtain LATP;

[0064] The chemical formula of LLTO (lithium lanthanum titanate) is Li 0.3 La 0.567 TiO3, the preparation method thereof is as follows: lithium carbonate, lanthanum oxide, and titanium oxide are weighed according to a molecular weight ratio (i.e., the molar ratio of lithium carbonate, lanthanum oxide, and titanium oxide is 0.15:0.28:1), mixed, and heat-treated at 1100° C. for 12 hours to obtain LLTO;

[0065] The chemical formula of LLZO (lithium lanthanum zirconium oxide) is Li 6.5 Ln3Z 1.5 O 12The preparation method is as follows: lithium carbonate, lanthanum oxide, and zirconium oxide are weighed according to a molecular weight ratio (i.e., the molar ratio of lithium carbonate, lanthanum oxide, and zirconium oxide is 3.25:1.5:1.5), mixed; heat treated at 900° C. for 6 hours to obtain LLZO;

[0066] Phenolic resin, commercially available.

[0067] Example 1

[0068] This embodiment provides a porous carbon, and the preparation method thereof comprises the following steps:

[0069] S1. Add 5 g of phenolic resin to 95 mL of anhydrous ethanol for dissolution, then add 0.15 g of electrolyte LLTO (lithium lanthanum titanate), dissolve and mix under ultrasonic for 30 min, and spray dry in a spray dryer at 110 ° C, a solution feed flow rate of 5 L / min, and an atomization pressure of 0.5 MPa to obtain a porous carbon precursor;

[0070] S2. The porous carbon precursor prepared in step S1 is placed in a CVD rotary furnace, and under the protection of argon, the temperature is raised to 700°C at 2°C / min, and kept at 700°C for 2h for pre-carbonization, and then the temperature is lowered to 400°C at 10°C / min, and then naturally cooled, and then the temperature is raised to 900°C at 5°C / min, and water vapor is introduced at 900°C for activation for 5h, thereby obtaining porous carbon;

[0071] In step S1, the mass ratio of the phenolic resin to the electrolyte LLTO is 100:3.

[0072] Examples 2-4 and Comparative Examples 1-2

[0073] Examples 2-4 and Comparative Examples 1-2 provide different porous carbons, which differ from Example 1 in that the mass ratios of the phenolic resin and the electrolyte LLTO (lithium lanthanum titanate) are different, and the rest are consistent with Example 1, as shown in the following table:

[0074] Table 1 Mass ratio of phenolic resin and electrolyte LLTO in Examples 1-4 and Comparative Examples 1-2

[0075]

[0076] Examples 5-8 and Comparative Examples 3-4

[0077] Examples 5-8 and Comparative Examples 3-4 provide different porous carbons, which differ from Example 1 in that the activation temperature in step S2 is different, and the rest are consistent with Example 1, as shown in the following table:

[0078] Table 2 Activation temperature in step S2 of Examples 1, 5-8 and Comparative Examples 3-4

[0079]

[0080]

[0081] Examples 9-12

[0082] Examples 9-12 provide different porous carbons, which differ from Example 1 in that the pre-carbonization temperature in step S2 is different, and the rest are consistent with Example 1, as shown in the following table:

[0083] Table 3 Pre-carbonization temperature in step S2 of Examples 1, 9-12

[0084] Pre-carbonization temperature in step S2 / °C Example 1 700 Example 9 800 Example 10 650 Embodiment 11 400 Example 12 900

[0085] Examples 13-14

[0086] Embodiments 13-14 provide different porous carbons, which differ from Embodiment 1 in that the type of electrolyte in step S1 is different, and the rest is consistent with Embodiment 1, as shown in the following table:

[0087] Table 4 Electrolyte types in step S1 of Examples 1, 13-14

[0088] Type of electrolyte in step S1 Example 1 LLTO (Lanthanum Lithium Titanate) Embodiment 13 LATP (lithium aluminum titanium phosphate) Embodiment 14 LLZO (lithium lanthanum zirconium oxide)

[0089] Embodiment 15

[0090] This embodiment provides a porous carbon, which differs from Example 13 in that 0.05g of electrolyte LATP (lithium aluminum titanium phosphate) is used instead of 0.15g of electrolyte LATP (lithium aluminum titanium phosphate), and the rest is consistent with Example 13.

[0091] Comparative Example 5

[0092] This comparative example provides a porous carbon, which differs from Example 1 in that spray drying is not performed in step S1, and the rest is consistent with Example 1, as follows:

[0093] S1. Add 5 g of phenolic resin to 95 mL of anhydrous ethanol for dissolution, then add 0.15 g of electrolyte LLTO (lithium lanthanum titanate), dissolve and mix by ultrasonication for 30 min, and then use a vacuum drying oven at 110 ° C to obtain a porous carbon precursor;

[0094] S2. The porous carbon precursor prepared in step S1 is placed in a CVD rotary furnace, and under the protection of argon, the temperature is raised to 700°C at 2°C / min, and kept at 700°C for 2h for pre-carbonization, and then the temperature is lowered to 400°C at 10°C / min, and then naturally cooled, and then the temperature is raised to 900°C at 5°C / min, and water vapor is introduced at 900°C for activation for 5h, thereby obtaining porous carbon;

[0095] In step S1, the mass ratio of the phenolic resin to the electrolyte LLTO is 100:3.

[0096] Comparative Example 6

[0097] This comparative example provides a porous carbon, which differs from Example 1 in that no pre-carbonization is performed in step S2, and the rest is consistent with Example 1, as follows:

[0098] S1. Add 5 g of phenolic resin to 95 mL of anhydrous ethanol for dissolution, then add 0.15 g of electrolyte LLTO (lithium lanthanum titanate), dissolve and mix under ultrasonic for 30 min, and spray dry in a spray dryer at 110 ° C, a solution feed flow rate of 5 L / min, and an atomization pressure of 0.5 MPa to obtain a porous carbon precursor;

[0099] S2. The porous carbon precursor prepared in step S1 is placed in a CVD rotary furnace, the temperature is raised to 900°C at 5°C / min, and water vapor is introduced at 900°C for activation for 5h to obtain porous carbon;

[0100] In step S1, the mass ratio of the phenolic resin to the electrolyte LLTO is 100:3.

[0101] Comparative Example 7

[0102] This comparative example provides a porous carbon, which differs from Example 1 in that water vapor is not introduced during activation in step S2, and the rest is consistent with Example 1, as follows:

[0103] S1. Add 5 g of phenolic resin to 95 mL of anhydrous ethanol for dissolution, then add 0.15 g of electrolyte LLTO (lithium lanthanum titanate), dissolve and mix under ultrasonic for 30 min, and spray dry in a spray dryer at 110 ° C, a solution feed flow rate of 5 L / min, and an atomization pressure of 0.5 MPa to obtain a porous carbon precursor;

[0104] S2. The porous carbon precursor prepared in step S1 is placed in a CVD rotary furnace, and under the protection of argon, the temperature is raised to 700°C at 2°C / min, and kept at 700°C for 2h for pre-carbonization, and then the temperature is lowered to 400°C at 10°C / min, and then naturally cooled, and then the temperature is raised to 900°C at 5°C / min, and activated at 900°C for 5h to obtain porous carbon;

[0105] In step S1, the mass ratio of the phenolic resin to the electrolyte LLTO is 100:3.

[0106] Application examples and comparative application examples

[0107] Application Example 1

[0108] This application example provides a nano silicon-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0109] S1. The porous carbon of Example 1 was placed in a fluidized bed, and nitrogen was continuously purged at a flow rate of 5 L / min to exhaust the air, and then the temperature was raised to 550°C at a flow rate of 10°C / min. On the basis of continuously passing nitrogen at a flow rate of 5 L / min, silicon source gas monosilane was passed at a flow rate of 2 L / min, and silicon was deposited on the porous carbon of Example 1 by chemical vapor deposition (CVD) for 5 hours to obtain a nano-silicon carbon precursor;

[0110] S2. On the basis of continuously introducing nitrogen at a flow rate of 5 L / min, the temperature was raised to 680°C at a flow rate of 10°C / min, and then the carbon source gas acetylene was introduced at a flow rate of 2 L / min. The nano-silicon carbon precursor was carbon-coated by chemical vapor deposition (CVD) for 2.5 hours, and naturally cooled to obtain the nano-silicon carbon negative electrode material.

[0111] Application Example 2-15

[0112] Application Example 2-15 provides different nano silicon carbon negative electrode materials. The difference between Application Example 2-15 and Application Example 1 is that Application Example 2-15 uses the porous carbon of Example 2-15 to replace the porous carbon of Example 1, and the rest is consistent with Application Example 1.

[0113] Comparative Application Examples 1-7

[0114] Comparative Application Examples 1-7 provide different nano-silicon carbon negative electrode materials. The difference between them and Application Example 1 is that Comparative Application Examples 1-7 use the porous carbon of Comparative Examples 1-7 to replace the porous carbon of Example 1, and the rest is consistent with Application Example 1.

[0115] Sample characterization

[0116] The porous carbon samples of Examples 1-15 and Comparative Examples 1-7 were characterized as follows:

[0117] (1) The method for measuring the median particle size (D50) of porous carbon is as follows: using a laser particle size analyzer - Mastersizer 3000 to test in accordance with the national standard GB / T 41949-2022;

[0118] (2) Method for measuring the specific surface area and pore size of porous carbon: Using nitrogen as adsorbent and TriStarⅡplus3030, the specific surface area of ​​porous carbon was tested according to the national standard GB / T 19587-2017, and the pore size of porous carbon was tested according to the national standard GB / T21650.2-2008;

[0119] The experimental results are shown in the following table:

[0120] Table 5 Characterization results of porous carbon samples of Examples 1-15 and Comparative Examples 1-7

[0121]

[0122] It can be seen from Table 5 that by comparing Examples 1, 5-8 and Comparative Examples 3-4, when the activation temperature of water vapor is too low, the pore size of the porous carbon will be too small, that is, the activation will be incomplete, which will affect the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano-silicon-carbon negative electrode material, which is not conducive to improving the capacity retention rate of the nano-silicon-carbon negative electrode material prepared using porous carbon and reducing the volume expansion of the nano-silicon-carbon negative electrode material during charging and discharging.

[0123] By comparing Examples 1 and 9-12, when the pre-carbonization temperature is too low, it will affect the carbonization degree of the porous carbon material, making the pore size of the porous carbon more likely to be smaller, and the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano-silicon-carbon negative electrode material are also more easily affected, and it is impossible to increase the capacity retention rate of the nano-silicon-carbon negative electrode material prepared by using the porous carbon and reduce the volume expansion of the nano-silicon-carbon negative electrode material during charging and discharging.

[0124] Performance Testing

[0125] The performance tests of the nano silicon carbon negative electrode materials of each application example and comparative application example are as follows:

[0126] (1) Preparation of button-type lithium-ion batteries

[0127] A1. Place the nano silicon carbon negative electrode material and conductive agent (acetylene black) of each application example or comparative application example in an oven, bake at 120°C for 4 hours, and then cool in a drying container; then, weigh the corresponding proportion of nano silicon carbon negative electrode material and conductive agent (acetylene black) according to the mass ratio of nano silicon carbon negative electrode material, binder (polyvinylidene fluoride), and conductive agent (acetylene black) of 80:10:10, add them to a 50mL small beaker, and then add the binder solution (5% N-methylpyrrolidone solution of polyvinylidene fluoride by mass fraction), and stir with a stirrer to form a paste;

[0128] A2. Apply the paste evenly on the aluminum foil to obtain a single-sided surface density of 60g / m 2 The negative electrode sheet was then placed in a blast drying oven and dried at 120°C for 2 hours and pressed (the pressing density of the negative electrode sheet was 2.0 g / cm 3 ), cut into a circular negative electrode sheet with a diameter of 12 mm;

[0129] A3. In an argon atmosphere glove box, a button-type lithium-ion battery was assembled with a circular negative electrode sheet as the negative electrode, a lithium sheet as the positive electrode, and a 1 mol / L LiPF6 ethylene carbonate solution and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 as the electrolyte;

[0130] (2) Measurement of first charge capacity, first cycle coulombic efficiency, and capacity retention rate after 10 cycles

[0131] At 25°C and 25% humidity, a charge and discharge test was performed on a button-type lithium-ion battery using a blue battery test system to measure the first charge capacity (first charge capacity) and first cycle coulomb efficiency of the button-type lithium-ion battery prepared using the nano silicon-carbon negative electrode material of each application example or comparative application example;

[0132] One charge and one discharge is one week, the first charge capacity is M1, and after 10 cycles, the charge capacity is M2. The capacity retention rate after 10 cycles is calculated by the formula [capacity retention rate after 10 cycles (%) = (M2 / M1) × 100%];

[0133] The present invention uses the capacity retention rate after 10 cycles to characterize the capacity retention rate of the nano silicon carbon negative electrode material. The greater the capacity retention rate after 10 cycles, the greater the capacity retention rate of the nano silicon carbon negative electrode material.

[0134] (3) Measurement method of the expansion rate of the first cycle with zero full charge

[0135] At 25°C, before assembling into a button-type lithium-ion battery, first measure the thickness H1 of the negative electrode (the nano silicon-carbon negative electrode material of each application example or comparative application example), then assemble into a button-type lithium-ion battery, and use the Blue Electric Battery Test System to perform a charge and discharge test on the button-type lithium-ion battery, discharge and charge once each, and then discharge the battery again, then disassemble the button-type lithium-ion battery in the glove box, and measure the thickness H2 of the negative electrode (the nano silicon-carbon negative electrode material of each application example or comparative application example), the first cycle zero full charge expansion rate (%) = (H2-H1) / H1×100%;

[0136] The present invention uses the first cycle zero-full charge expansion rate to characterize the volume expansion of the nano silicon-carbon negative electrode material during charging and discharging; the larger the first cycle zero-full charge expansion rate, the larger or more serious the volume expansion of the nano silicon-carbon negative electrode material during charging and discharging;

[0137] The experimental results are shown in the following table:

[0138] Table 6 Performance test results of nano silicon carbon negative electrode materials in various application examples and comparative application examples

[0139]

[0140]

[0141] As can be seen from Table 6, the preparation method of porous carbon of the present invention improves the interface condition of the nano silicon carbon negative electrode material prepared using porous carbon, inhibits the generation of new SEI film, improves the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon, and reduces the volume expansion of the nano silicon carbon negative electrode material during charging and discharging by controlling the mass ratio of resin and electrolyte and the activation temperature of water vapor. At the same time, the brittleness and pore size of the porous carbon are also regulated by controlling the activation temperature of water vapor, which is beneficial to improving the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon and reducing the volume expansion of the nano silicon carbon negative electrode material during charging and discharging.

[0142] Specifically, by comparing Application Examples 1-4 and Comparative Application Examples 1-2, it can be seen that when the mass ratio of the resin and the electrolyte is too high or too low, it is not conducive to improving the interface conditions of the nano-silicon carbon negative electrode material, cannot inhibit the formation of the SEI film, cannot improve the capacity retention rate of the nano-silicon carbon negative electrode material prepared using porous carbon, and cannot reduce the volume expansion of the nano-silicon carbon negative electrode material during charging and discharging.

[0143] By comparing application examples 1, 5-8 and comparative application examples 3-4, it can be seen that when the activation temperature of water vapor is too high or too low, it is not conducive to improving the interface conditions of the nano silicon carbon negative electrode material, and it is impossible to inhibit the formation of the SEI film, and it is impossible to improve the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon and reduce the volume expansion of the nano silicon carbon negative electrode material during charging and discharging; in addition, when the activation temperature of water vapor is too high, it will also increase the brittleness of the porous carbon, making the porous carbon prone to fragmentation and structural collapse, which is not conducive to improving the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon and reducing the volume expansion of the nano silicon carbon negative electrode material during charging and discharging; and when the activation temperature of water vapor is too low, it will also make the pore size of the porous carbon smaller, that is, the activation is incomplete, which affects the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano silicon carbon negative electrode material, which is not conducive to improving the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon and reducing the volume expansion of the nano silicon carbon negative electrode material during charging and discharging.

[0144] By comparing application examples 1, 9-12, it can be seen that if the pre-carbonization temperature is too high, the brittleness of the porous carbon will increase, making the porous carbon more prone to cracking and structural collapse, and it is impossible to increase the capacity retention rate of the nano silicon carbon negative electrode material prepared using the porous carbon to a greater extent, and reduce the volume expansion of the nano silicon carbon negative electrode material during charging and discharging; if the pre-carbonization temperature is too low, it will affect the carbonization degree of the porous carbon material, making the pore size of the porous carbon more likely to be smaller, and the silicon deposition and carbon coating of the porous carbon in the process of preparing the nano silicon carbon negative electrode material are also more easily affected, and it is impossible to increase the capacity retention rate of the nano silicon carbon negative electrode material prepared using the porous carbon to a greater extent, and reduce the volume expansion of the nano silicon carbon negative electrode material during charging and discharging.

[0145] By comparing Application Example 1 and Comparative Application Examples 5-7, it can be seen that when preparing porous carbon in the present invention, if spray drying or pre-carbonization or water vapor is not introduced during activation, it will be unfavorable to improve the capacity retention rate of the nano silicon carbon negative electrode material prepared using porous carbon and reduce the volume expansion of the nano silicon carbon negative electrode material during charging and discharging.

[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing porous carbon, characterized in that: The preparation method comprises the following steps: S1. mixing a resin and an electrolyte in a solvent, and obtaining a porous carbon precursor by spray drying; S2. Pre-carbonizing the porous carbon precursor and then activating it with water vapor to obtain porous carbon; In step S1, the mass ratio of the resin to the electrolyte is 100:(0.1-5); In step S2, the activation temperature is 500-1200°C.

2. The method for preparing porous carbon according to claim 1, characterized in that: Include at least one of the following (1)-(2): (1) In step S1, the mass ratio of the resin to the electrolyte is 100:(1-5); (2) In step S2, the activation temperature is 600-1100°C.

3. The method for preparing porous carbon according to claim 1, characterized in that: Including at least one of the following (1)-(3): (1) In step S2, the pre-carbonization temperature is 400-900°C; (2) In step S1, the electrolyte is at least one of LATP, LLTO and LLZO; (3) In step S1, the resin is at least one of polyester resin, polyamide resin, phenolic resin, and polyvinyl chloride resin.

4. A porous carbon, characterized in that The product is prepared by the preparation method described in any one of claims 1 to 4.

5. The porous carbon according to claim 4, characterized in that: The median particle size (D50) of the porous carbon is 1.5-15 μm, and the specific surface area is 800-2000 m 2 / g, pore size is 0.5-2nm.

6. Use of the porous carbon according to any one of claims 4 to 5 in negative electrode materials.

7. A method for preparing a nano silicon-carbon negative electrode material, characterized in that: The preparation method comprises the following steps: S1. Under inert gas protection, silicon is deposited on the porous carbon according to any one of claims 4-5 by chemical vapor deposition using a silicon source gas to obtain a nano-silicon carbon precursor; S2. Under the protection of inert gas, the nano silicon carbon precursor is carbon coated by using carbon source gas through chemical vapor deposition to obtain the nano silicon carbon negative electrode material.

8. The method for preparing the nano silicon carbon negative electrode material according to claim 7, characterized in that: Include at least one of the following (1)-(2): (1) In step S1, the silicon source gas is at least one of monosilane, disilane, dichlorosilane, silicon tetrachloride, dichlorodihydrosilane, and trichlorosilane; (2) In step S2, the carbon source gas is at least one of acetylene, methane, propane, and cyclohexane.

9. The method for preparing the nano silicon carbon negative electrode material according to claim 7, characterized in that: Include at least one of the following (1)-(2): (1) In step S1, the silicon deposition temperature is 400-700° C. and the time is 1-6 hours; (2) In step S2, the carbon coating is carried out at a temperature of 400-800°C and for a time of 1-6 hours.

10. A nano silicon carbon negative electrode material, characterized in that: The product is prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • High-conductivity silicon-oxygen negative electrode material and application thereof

    CN111048756A

  • Preparation method of sodium ion battery positive electrode material and prepared material

    CN113135561A

  • Preparation method of silicon-carbon negative electrode material of lithium ion battery

    CN115275149A

  • Amorphous silicon-carbon composite material, preparation method and application thereof, and lithium ion secondary battery

    CN115995542A

  • Preparation method and application of amorphous silicon-based negative electrode material

    CN116281943A

Cited By

  • Preparation method of high-capacity silicon-carbon negative electrode material

    CN120057924A

  • Preparation method of high-capacity silicon-carbon negative electrode material

    CN120057924B